2017
DOI: 10.1038/s41598-017-03271-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF) levels are associated with hyperglycemia and β cell dysfunction in a Chinese population

Abstract: Several recent clinical studies have suggested that the levels of circulating 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF) are significantly higher in patients with gestational diabetes mellitus (GDM), impaired glucose tolerance (IGT), and type 2 diabetes mellitus (T2DM). This study recruited a total of 516 participants. The following patient populations were enrolled: 99 newly diagnosed cases with T2DM, 219 cases with prediabetes [82 with isolated impaired glucose tolerance (I − IGT), 66 with isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…This observation is in line with the reported beneficial effects of Lovaza on regulation of lipid profiles in humans, suggesting that CMPF may be an active component of FO, contributing to the beneficial metabolic effects seen in humans. Interestingly, human studies have also revealed a strong correlation between elevated circulating CMPF and reduced plasma TG levels, associating CMPF with a role in regulating glycolipid metabolism …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is in line with the reported beneficial effects of Lovaza on regulation of lipid profiles in humans, suggesting that CMPF may be an active component of FO, contributing to the beneficial metabolic effects seen in humans. Interestingly, human studies have also revealed a strong correlation between elevated circulating CMPF and reduced plasma TG levels, associating CMPF with a role in regulating glycolipid metabolism …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, human studies have also revealed a strong correlation between elevated circulating CMPF and reduced plasma TG levels, associating CMPF with a role in regulating glycolipid metabolism. [14][15][16] Mechanistically, CMPF was found to be an inhibitor of acetyl-coA carboxylase (ACC), the master regulator of fatty acid metabolism, as well as having the ability to induce the production of fibroblast growth factor 21 (FGF21). 9 CMPF's long-term preventive effect on HFDinduced hepatic lipid accumulation is absent in FGF21KO mice, suggesting that the long-term beneficial effect of CMPF on metabolism is FGF21 dependent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the same team found that elevated CMPF caused the formation of advanced glycation end‐products, which are known to impair insulin secretion, and increased fatty acid oxidation. This result might explain why CMPF showed an independent negative association with triglycerides in previous studies of individuals with disturbances in carbohydrate metabolism. However, we found that the negative association between CMPF and triglycerides was also present in individuals with NGT in addition to type 2 diabetes mellitus patients.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, in vitro experiments using human embryonic kidney 293 cells and mouse primary hepatocytes found that CMPF had no intrinsic cytotoxicity in either cell line, and did not inhibit CYP3A4, CYP2D6 or CYP2C9. Furthermore, a study of 516 participants showed an independent and inverse association between CMPF and triglycerides. Cumulatively, these findings show an important role of CMPF as a harmless metabolite involved in the regulation of lipid metabolism, and suggest that it is not cytotoxic to the liver.…”
Section: Introductionmentioning
confidence: 99%